A Review on the Self-Cleansing Design Criteria for Sewer System - Bong, C.H.J (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Sediment deposits in sewer system had been known to have adverse effects on the hydraulic performance of the system and also on the environment. Thus, the need for sewer system to carry sediment has been recognized for many years and self-cleansing criteria have been proposed in the literature for design purposes. Conventionally, a minimum critical velocity or critical shear stress was specified and although this approach had been successful in many cases; it was appreciated that a minimum critical velocity or critical shear stress which is unrelated to the characteristics and concentration of the sediment or the hydraulic behavior of the sewer could not properly represent the ability of the sewer flows to transport sediments. A more viable approach for self-cleansing design is to incorporate some aspect of the sediment and sewer characteristics into the design criteria; hence, various self-cleansing design criteria for sewer have been proposed in the literature. This paper presents a review on the various self-cleansing design criteria for sewer and proposed some further studies that could be conducted to improve the existing self-cleansing design criteria.